Juxtaposing the Brain and Belief - Ashbrook, James B. (Journal of psychology and theology, 1984)
To juxtapose the brain and belief sheds new light on puzzling patterns of belief. The brain works in two ways: a stabilizing step-by-step process and a variety-generating all-at-once process. Patterns of belief also present two kinds of focal meaning: setting-right of reality through the interpretations and imperatives of the proclamation of the Gospel and making-real of reality through the experiences and symbolizations of God's manifestations of himself. “Mind” provides an analytic metaphor which relates these processes of the brain and patterns of belief. As an organized whole, the brain reveals regularities. As part of a larger whole, the mind generates emergent features. Just as the mind is the human meaning of the brain, so God is the theological referent of the mind. The goodness and sovereignty of God are reflected in our one brain with its two ways of working. That which is most fully “us” is that which is most truly “real.”